Passivation Effect of CsPbI3 Quantum Dots on the Performance and Stability of Perovskite Solar Cells - Genjie Yang; Dianli Zhou; Jiawen Li; Junsheng Yu (Photonics, 2021)
The quality of active layer film is the key factor affecting the performance of perovskite solar cells. In this work, we incorporated CsPbI3 quantum dots (QDs) materials into the MAPbI3 perovskite precursor to form photoactive layer. On one hand, CsPbI3 QDs can be used as nucleation center to enhance the compactness of the perovskite film, and on the other hand, partially CsPbI3 QDs can be dissociated as anions and cations to passivate vacancy defects in the perovskite active layer. As a result, the film quality of the active layer was improved remarkably, thus exciton recombination was reduced, and carrier transfer increased accordingly. The devices based on doped-CsPbI3 QDs film had higher short circuit current, open circuit voltage and filling factor. Finally, the power conversion efficiency (PCE) was greatly enhanced from 14.85% to 17.04%. Furthermore, optimized devices also exhibited better stability. This work provides an effective strategy for the processing of high-quality perovskite films, which is of great value for the preparation and research of perovskite photoelectronic devices.